WATER POLICIES AND FARMERS VULNERABILITY IN GROUNDWATER IRRIGATION SYSTEMS - Fabrice Paulin Ketchagmen Fosso, Gozen Elkiran (Chelonian Research Foundation, 2024)
Throughout most dry and dry parts of worldwide, increased rivalry to supplies of water is turning into an interpersonal, financial, and conservation problem. It's a significant issue in additional dry nations in Europe (such as Spain), the African continent (South Africa, Namibia, and Botswana), and other parts of the world where water consumption, habitat loss, and lack of water are all becoming socially concerning. While social anxieties about the national allocation of water ownership and ecological problems steadily develop in such nations, water challenges and local rivalries to water begin to take center stage on legislative plans and discussions in society. Groundwater supplies, that are becoming scarcer in a lot of cities worldwide, are becoming increasingly important to producers and the numerous businesses that rely on their crops. From cultivating foods that use fewer resources or using the best methods of irrigation, farmers may lower the amount of water they use. Their decisions may have far-reaching effects on farms. The effects and repercussions of excessive water limitations are examined in this paper across particular fields. Together with those involved in agriculture in so many nations, the examination was completed. Financial and technological analyses of the methods and modifications made by growers and daily consumers of water have been carried out in order to address the limited supply of the resource. Interactive seminars emphasized the relationships across owners within a particular category and also among distinct industries by bringing together various operators who may end up competing for an identical asset. Key words: irrigation, water policies, vulnerability assessment, sustainable crops.